Mapping factors associated with emotional and behavioral problems among preschool children: A scoping review protocol - Esme Anggeriyane; Siti Yuyun Rahayu Fitri; Meita Dhamayanti; Windy Rakhmawati; Bella Mardya (PLoS ONE, 2026)
Emotional and behavioral problems in preschool children are increasingly regarded as a major public health concern, particularly as early life challenges can lead to long-lasting difficulties in later childhood and adulthood. Although numerous studies have examined the factors associated with EBPs, the evidence remains fragmented across disciplines, study designs, and measurement approaches, limiting a coherent understanding. This scoping review aims to systematically map and synthesize factors associated with emotional and behavioral problems in preschool children. This scoping review will follow the methodological framework proposed by Peters (2020), in accordance with the Joanna Briggs Institute (JBI) guidance, and documented in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Scoping Reviews (PRISMA-ScR) guidelines. A systematic search will be undertaken in PubMed, Scopus, Web of Science (WoS), the Cochrane Library, Embase, and EBSCOhost (via MEDLINE and CINAHL) for studies published from 2000 onwards. Qualitative, quantitative, and mixed-methods studies, with no language restrictions, will be included. Study selection and data charting will be independently conducted by at least two reviewers, with disagreements resolved through discussion. Data will be synthesized using a descriptive analytical approach, with factors categorized into genetic, biological, psychological, and environmental domains. Findings will be presented through narrative synthesis and summary tables, with frequency mapping and thematic grouping used to identify patterns, variations in measurement approaches, and evidence gaps. This review will provide a comprehensive overview of how factors associated with EBPs in preschool children have been studied and will inform future research, policy, and early prevention strategies.